2018
DOI: 10.1186/s40902-018-0176-y
|View full text |Cite
|
Sign up to set email alerts
|

Orthognathic surgery for patients with fibrous dysplasia involved with dentition

Abstract: BackgroundFibrous dysplasia (FD) is characterized by the replacement of normal bone by abnormal fibro-osseous connective tissue and typically treated with surgical contouring of the dysplastic bone. When dysplastic lesions involve occlusion, not only is surgical debulking needed, orthognathic surgery for correction of dentofacial deformity is mandatory. However, the long-term stability of osteotomized, dysplastic bone segments is a major concern because of insufficient screw-to-bone engagement during surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Navigation was used by Matsuao et al 9 and Heiland et al 10 with a contradictory conclusion for safety and limitation of its application. A review done by Udaykumar et al 11 in 2018 only 15 cases are reported of FD with dentoskeletal asymmetry correction. Gross facial deformity with social problems may be an indication for an early intervention but it is suggested to intervene for debulking after the skeletal maturity and secondary correction only after orthodontic decompensation to rule out interferences during maxillary cant correction.…”
Section: Discussionmentioning
confidence: 99%
“…Navigation was used by Matsuao et al 9 and Heiland et al 10 with a contradictory conclusion for safety and limitation of its application. A review done by Udaykumar et al 11 in 2018 only 15 cases are reported of FD with dentoskeletal asymmetry correction. Gross facial deformity with social problems may be an indication for an early intervention but it is suggested to intervene for debulking after the skeletal maturity and secondary correction only after orthodontic decompensation to rule out interferences during maxillary cant correction.…”
Section: Discussionmentioning
confidence: 99%
“…e surgical management varies according to patient. [1][2][3][4]6] In prepubertal age, wait is advised till puberty; unless there is functional loss. After puberty, FD growth slows down and excision gives better results.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In McCune Albright syndrome and pediatric population, growth hormone excess is found to be cause of extensive FD. [1,4] CONCLUSION Despite its benign nature, craniofacial FD has a tendency to recur after surgery. Frontal FD recurrence occurs due to missed lesion at deeper or difficult locations, for example, in sinus area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment for FD is limited to cases involving esthetic or functional problems. It is recommended when FD poses a threat to important anatomical structures, such as the eyes or the optic nerves, causes significant esthetic deformities, or if severe pain is clearly associated with the FD process [ 24 ]. In some cases, cosmetic trimming of excess bone may be required [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%